Structure and evolution of the upper mantle of the Australian Plate and North Atlantic Ocean from waveform tomography - De Laat, Johanneke Iza (Trinity College Dublin. School of Natural Sciences. Discipline of Geology, 2023)
APPROVED With the expansion of regional and global seismic networks and the advancing of tomographic techniques, tomography models are able to reveal the heterogeneities in the Earth's interior with an increasing amount of detail. Illuminating the seismic velocity anomalies within the Earth contributes to our understanding of the structure, dynamics and evolution of the Earth. The lack of seismic data that covers the world's oceans, however, is a factor that limits the resolution of tomography models. In this thesis, two new regional upper mantle tomography models of S-wave velocity and azimuthal anisotropy are presented. These tomography models are computed using a global dataset of 1.7 million waveforms. New seismic data was obtained by the deployment of an array of ocean bottom seismometers (OBSs) in the North Atlantic Ocean. The waveforms were successfully fit using the Automated Multimode Inversion (AMI), which fits S-, multiple S- and Rayleigh waves. AMI computes a set of linear independent equations for each seismogram, describing the perturbations of P- and S-waves within their sensitivity kernels between the source and the receiver. These equations are combined in a large linear system and inverted for the 3D global distribution of P- and S-waves and S-wave azimuthal anisotropy in the upper mantle. To avoid errors in the model, the least consistent measurements of the dataset were identified and removed from the global inversion. The two tomography models were each computed using a subset of the global database, discarding the waveforms that have both their source and their receiver outside the hemisphere surrounding the research area. The models were optimized for the region of interest by optimizing the parameter settings for the area and by performing area-specific outlier analysis. A new tomography model of the Australian plate and its boundaries, Aus22, is presented. The model is validated by performing resolution tests and, for specific locations, by computing Rayleigh phase velocities using ...